Mood and Modalities Revealing Teacher’s Power in EFL Classroom Discourse: Critical Discourse Analysis - Surjowati, Ribut; Wirawati, Bekti; Shalsadita, Ratu Tria; Achmad, Shafira Aulia (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This research aims to describe how power relation is exercised through mood and modality used by lecturers during the teaching and learning process in the classrooms. It is categorized as descriptive qualitative research, and the data were collected from the utterances of the English Education lecturers through non-participant observation. They were then analyzed by following three stages of Fairclough CDA. The analysis was done from textual to social practice analysis to reveal the relation between the utterance and power the lecturers practiced in the classrooms. The research finding reveals that the power is reflected through the use of imperative, interrogative, and declarative mood structures. Modality is realized through modal auxiliaries: will, would, can, must, could, may, should, and verbs; have to, think, had better, need to, be sure, perhaps, and be going to. Those expressions carry the meaning of volition, obligation, encouragement, permission, demand, and possibilities employed by the lecturers in the classes. The above meanings of those expressions represent the lecturers’ power over the students. The built power relation represents Indonesian culture in which those in higher positions play as superiors. Examining modality and mood expressions used in education will hopefully give an insight into how to build good communication.